A Decadal (2002–2014) Analysis for Dynamics of Heterotrophic Bacteria in an Antarctic Coastal Ecosystem: Variability and Physical and Biogeochemical Forcings - Kim, Hyewon; Ducklow, Hugh W. (Frontiers in Marine Science, 2016)
We investigated the dynamics of heterotrophic bacteria in the coastal western Antarctic Peninsula (WAP), using decadal (2002–2014) time series of two bacterial variables, bacterial production (BP) via 3H-leucine incorporation rates and bacterial biomass (BB) via bacterial abundance, collected at Palmer Antarctica Long Term Ecological Research (LTER) Station B (64.8°S, 64.1°W) over a full austral growing season (October–March). Strong seasonal and interannual variability in the degree of bacterial coupling with phytoplankton processes were observed with varying lags. On average, BP was only 4% of primary production (PP), consistent with low BP:PP ratios observed in polar waters. BP was more strongly correlated with chlorophyll (Chl), than with PP, implying that bacteria feed on dissolved organic carbon (DOC) produced from a variety of trophic levels (e.g., zooplankton sloppy feeding and excretion) as well as directly on phytoplankton-derived DOC. The degree of bottom-up control on bacterial abundance was moderate and relatively consistent across entire growing seasons, suggesting that bacteria in the coastal WAP are under consistent DOC limitation. Temperature also influenced BP rates, though its effect was weaker than DOC. We established generalized linear models (GLMs) for monthly composites of BP and BB via stepwise regression to explore a set of physical and biogeochemical predictors. Physically, high BP and large BB were shaped by a stratified water-column, similar to forcing mechanisms favoring phytoplankton blooms, but high sea surface temperature (SST) also significantly promoted bacterial processes. High BP and large BB were influenced by high PP and bulk DOC concentrations. Based on these findings, we suggest an increasingly important role of marine heterotrophic bacteria in the coastal WAP food-web as climate change introduces a more favorable environmental setting for promoting BP, with increased DOC from retreating glaciers, a more stabilized upper water-column from ice-melt, and a baseline shift of water temperature due to more frequent delivery of warming Upper Circumpolar Deep Water (UCDW) onto the WAP shelf.